Biosynthesis of providencin: Understanding photochemical cyclobutane formation with density functional theory - Tang, B; Paton, R (American Chemical Society, 2019)
The unique structure of furanocembranoid natural product providencin has stimulated biosynthetic hypotheses, especially concerning the formation of its cyclobutanol ring. One such hypothesis involves a photochemically induced Norrish–Yang cyclization in bipinnatin E. We have used computations to assess the feasibility and the stereochemical outcome of this proposed biosynthetic transformation. Density functional theory calculations reveal that the proposed Norrish–Yang cyclization in bipinnatin E is possible and that the stereoselectivity of this step is consistent with that of the natural product.